Design and performance analysis of a charge controller for solar system using MATLAB/SIMULINK - Samuel, Isaac A.; Izi, Oghenekome; Somefun, Tobiloba E.; Awelewa, Ayokunle A.; Katende, James (Frontiers in Energy Research, 2022)
The energy utilization of a Photovoltaic (PV) module is determined by the maximum power the module harnesses from the sun. A static PV module can only harness maximum power from the sun at a particular time in a day as the sun revolves. This simply means that if the PV module can be designed to move in such a direction to harness maximum power from the sun, then its energy utilization efficiency will be highly improved over the period the Sun is available. This design can be achieved by employing Perturb and Observe (P and O) algorithm for maximum power point tracking (MPPT). In this study, Propotional and Integral (PI) controller along with P and O is proposed to solve the problem of low efficiency and irregular output oscillations. The simulation is carried out in the MATLAB/SIMULINK environment and the result shows that by incorporating the PI controller into the system, the efficiency of 99.96% at the maximum power point was attained.